Miners and merchants in the Central Andes of Alto Marañón. Notes on the victorious crusade of mercantile capital and the impact of Cádiz liberalism between Llata and Huallanca: 1775-1830 - Espinoza Claudio, César (2020)
This essay explores the social, economic, and political life of indigenous and creole people from a Peruvian region amid the central Andes and the Amazon. We depict the rise and fall of the viceregal organization, looking into the political conflicts within the Huamalíes province, involving two social forces that not only broke that viceregal organization but were committed to organizing another way of governing the region adding the political participation of indigenous communities. Thus, we describe and analyze confrontations between the landowner Marques de Copa with the political resistance of Huallanca’s mining colonizers, explain the political meaning of a temporary triumph from the Caballeros Huallanquinos, and their political influence through the Alto Marañón territory. Finally, we present life stories linked to politics, mining, and livestock economy.